Antimicrobial resistance of Streptococcus pneumoniae from invasive pneumococcal diseases in Latin American countries: a systematic review and meta-analysis - María Macarena Sandoval; Silvina Ruvinsky; Silvina Ruvinsky; María Carolina Palermo; Tomás Alconada; Martín Eduardo Brizuela; Martín Eduardo Brizuela; Eugenia Ramirez Wierzbicki; Joaquín Cantos; Ariel Bardach; Ariel Bardach; Agustín Ciapponi; et al. (Frontiers Media S.A., 2024)
BackgroundInvasive pneumococcal disease has declined since pneumococcal conjugate vaccine introduction in Latin America and the Caribbean (LAC). However, serotype distribution and antimicrobial resistance patterns have changed.MethodsWe conducted a systematic review to evaluate the frequency of antimicrobial resistance of Streptococcus pneumoniae from invasive disease in LAC. Articles published between 1 January 2000, and 27 December 2022, with no language restriction, were searched in major databases and gray literature. Pairs of reviewers independently selected extracted data and assessed the risk of bias in the studies. The quality of antimicrobial resistance (AMR) studies was evaluated according to WHO recommendations (PROSPERO CRD42023392097).ResultsFrom 8,600 records identified, 103 studies were included, with 49,660 positive samples of S. pneumoniae for AMR analysis processed. Most studies were from Brazil (29.1%) and Argentina (18.4%), were cross-sectional (57.3%), reported data on AMR from IPD cases (52.4%), and were classified as moderate risk of bias (50.5%). Resistance to penicillin was 21.7% (95%IC 18.7-25.0, I2: 95.9), and for ceftriaxone/cefotaxime it was 4.7% (95%IC 3.2-6.9, I2: 96.1). The highest resistance for both penicillin and ceftriaxone/cefotaxime was in the age group of 0 to 5 years (32.1% [95%IC 28.2-36.4, I2: 87.7], and 9.7% [95%IC 5.9-15.6, I2: 96.9] respectively). The most frequent serotypes associated with resistance were 14 for penicillin and 19A for ceftriaxone/cefotaxime.ConclusionApproximately one-quarter of invasive pneumococcal disease isolates in Latin America and the Caribbean displayed penicillin resistance, with higher rates in young children. Ongoing surveillance is essential to monitor serotype evolution and antimicrobial resistance patterns following pneumococcal conjugate vaccine introduction.